Crossing empire's edge : Foreign Ministry police and Japanese expansionism in Northeast Asia - Esselstrom, Erik (The world of East Asia., 2009)
For more than half a century, the Japanese Ministry of Foreign Affairs (Gaimusho) possessed an independent police force that operated within the space of Japan's informal empire on the Asian continent. This text reveals its complex history.